2007
DOI: 10.1214/ejp.v12-438
|View full text |Cite
|
Sign up to set email alerts
|

Large deviations for the largest eigenvalue of rank one deformations of Gaussian ensembles

Abstract: Abstract. We establish a large deviation principle for the largest eigenvalue of a rank one deformation of a matrix from the GUE or GOE. As a corollary, we get another proof of the phenomenon, well-known in learning theory and finance, that the largest eigenvalue separates from the bulk when the perturbation is large enough. A large part of the paper is devoted to an auxiliary result on the continuity of spherical integrals in the case when one of the matrix is of rank one, as studied in [9].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 16 publications
2
73
0
Order By: Relevance
“…In this regime the typical value µ typ M of the smallest eigenvalue is out of bulk and equals to µ 0 (θ, β), see (52) and (74). Given the functions:…”
Section: Large Deviation Function Optimized Over U At Fixed θmentioning
confidence: 95%
“…In this regime the typical value µ typ M of the smallest eigenvalue is out of bulk and equals to µ 0 (θ, β), see (52) and (74). Given the functions:…”
Section: Large Deviation Function Optimized Over U At Fixed θmentioning
confidence: 95%
“…In the case of the GUE, this was due to Peché, 37 while a rigorous study of the GOE case can be found in the work of Maida. 30 The paper by Baik et al 5 proved the phase transition property relating to ͑1.2͒ in the complex case with ⌺ given by ⌺ = diag͑͑b͒ r , ͑1͒ m−r ͒ ͓͑1.4͒ corresponds to r =1͔. Subsequent studies by Baik and Silverstein, 6 Paul, 36 and Bai and Yao 4 considered the real case.…”
Section: B Related Workmentioning
confidence: 99%
“…Therefore we only need to estimate small ball probabilities around x = 2. Asμ X N concentrates at the scale N, and ||X N || is exponentially tight at the scale N by Assumption 1.2 it is enough to show that for any K > 0, [16,Proposition 2.1], we know that the spherical integral is continuous, more precisely, for N large enough and any X N ∈ V δ,x ,…”
Section: Remark 13mentioning
confidence: 99%